Hubungan Kompensasi dan Kinerja Karyawan terhadap Produktifitas melalui Pendekatan Analisis Kanonikal - Nurvi Oktiani (LPPM Universitas BSI, 2022)
Turbulance in Management unconsciously has created a challenge in public sector and private sector for managing enterprises, so that undergoing all of vision which have been set and in the end can increase productivity, as for the purpose of research is knowing relationship between compesation, performance of employee toward productivity. The method research uses Quallitantif design and analytic data uses Canonical corellation, the sources of data has been obtained by Questionnaire distribution with taking some sample with amount 34 employee or staffing from .PT Gotrans Logistics International The result of Research have been proved that Individual test and Group test with Canonical Analysis describe between compensation, performance employee toward productivity have significance relationship, however they need attention especially for compensation function whereas the implementation of Compensation function, because the compensation is still implementated amount 0.29946 less than performancen of employee with amount 0.7236, and advice for this result as a entreprises can increase and develop for implementating the compensation function Keywords: Compensation, performance, productivity